Penerapan Pendidikan Karakter Di Madrasah Aliyah Yayasan Ittihadiyah Kecamatan Medan Johor Kotamadya Medan - Ahmad Darwis; Juliandi Juliandi; Siti Derhana (Yayasan Rahmat Islamiyah, 2021)
The application of character education in madrasas or schools needs to be done integrally between learning methods, material and rules that exist in madrasas or schools. This research is motivated by the need for strong motivation in order to grow his character in learning. The low motivation of students' learning enthusiasm coupled with the habit of cheating, being undisciplined and not being present in learning activities shows that the application of character education is not integral. The application of character education must be carried out thoroughly, the need for cooperation and engagement between teachers, leaders, guardians of students and students. This research was conducted by conducting field surveys, interviews with teachers, and library research. This type of research is qualitative. The application of character education will work well if school leaders and teachers understand and apply it in a comprehensive learning process and school activities.